The Pyrolytic Decomposition of 6,6-Dimethyl-2-Cyclohexen-OL Acetate: A Study of the Thermal Elimination of Allylic Esters - Lam, Leo Ka-Ming (My University, 1963)
The acetate of 6,6-dimethyl-2-cyclohexen-l-ol was thermally decomposed and the pyrolysis products were characterized. This allylic ester decomposed with difficulty. Under conditions which led to complete decomposition of 3-acetoxcyclo-hexene, 6,6-dimethy-2-cyclohexene-l-ol acetate was virtually unreacted. Complete decomposition of the allylic acetate was achieved at about 600°C. The pyrolysis products consisted mainly of o-xylene, toluene, 5,5-dimethyl-l,3-cyclohexadiene and acetic acid. The aromatic compounds are thought to be formed from the less stable diene. Partial decomposition of ester enriched with deuterium in the 4-position, permitted estimation of the isotope effect, Ku/kD, for the pyrolytic elimination. The value obtained was about 2. Together with other experimental evidence, it indicates that the main mode of decomposition is 1,4-conjugate elimination and that allylic rearrangement, if it occurs at all, is unimportant.
Keywords: pyrolytic decomposition; 6,6-Dimethyl-2-cyclohexen-l-ol; thermal elimination; allylic esters